Unilateral Papillitis as the Initial Presentation of Hemifacial Atrophy: Case Report and Review of Literature (Bangladesh Journal of Neurosurgery, 2020)
Papillitis is a vision threatening condition, characterized by inflammation of the optic disc which often mimicked the features of papilledema; hence these patients often referred to the Neurosurgeon to exclude any intracranial pathology. This entity is associated with a number of intracranial, as well as extracranial pathologies. Among them, Parry–Romberg syndrome, also known as progressive hemifacial atrophy (PHA) possesses multiple ophthalmologic and neurologic manifestations. Here we report the case of a 14-year-old girl, who presented with the feature of progressive dimness of vision involving the right eye. Thorough physical examination demonstrated features of PHA overlapping with papillitis on fundoscopic examination. The patient treated with steroids, following which there was visual improvement. After evaluation in our facility, she was referred to department of plastic and reconstructive surgery for aesthetic improvement.Bang. J Neurosurgery 2020; 10(1): 97-101